Crofters and habitants : settler society, economy, and culture in a Quebec Township, 1848-1881 - Little, J. I. (John Irvine), 1947- (Studies on the history of Quebec., 1991)
The two groups arrived in Winslow Township in the middle of the nineteenth century, when modern state bureaucracy was just developing in Lower Canada (Quebec). Little was therefore able to examine a wealth of material from the departments responsible for crown lands, public works, and education as well as comprehensive data from the registry offices and manuscript census reports. This state-generated material, as well as a rich collection of Catholic and Presbyterian church records and documents from Scotland, provides the basis for a detailed analysis of society, economy, and culture in one isolated pocket of colonization. Little focuses on settlement patterns, population expansion and mobility, family structure and inheritance, farm production and labour, the role played by local merchants and millers, and the cultural significance of religion and education. He documents the differences which can be traced to ethnic origin but emphasizes the many similarities which characterized the adjustment of the two groups. Economic development in this geographical area was severely restricted by thin soil, rugged topography, and a brutally short growing season, coupled with the government's favouritism towards monopolistic lumber companies. Two viable communities did, nevertheless, take root, each drawing heavily on traditional cultural values and a history of economic resourcefulness in order to survive in an era of emerging industrial capitalism.